Perceived Organizational Support and Work Engagement: Testing the Mediating Role of Perceived Insider Status in Indonesia - Raissa Aurely; Zamralita Zamralita; Reza Fahlevi (International Journal of Multidisciplinary Research of Higher Education, 2026)
Employee engagement in work is key to organizational success, yet only 21% of employees globally are truly engaged in their work, reflecting a major challenge in human resource management. This research aims to examine the mediating role of Perceived Insider Status (PIS) in the relationship between Perceived Organizational Support (POS) and Work Engagement among employees in Indonesia. This research uses a quantitative method with a cross-sectional design, involving 283 employee participants who met the research criteria. Data were collected through online surveys using validated instruments: Utrecht Work Engagement Scale (UWES), Survey of Perceived Organizational Support (SPOS), and Perceived Insider Status Scale. Analysis results using PROCESS bootstrapping regression indicate that POS has a significant and positive effect on work engagement (β = 0.1194, p < 0.001) and POS also has a significant effect on PIS (β = 0.0388, p < 0.001). However, PIS does not have a significant effect on work engagement (β = -0.3351, p = 0.0942 > 0.05), thus PIS was not proven to function as a mediating variable (indirect effect: β = -0.0130, 95% CI [-0.0361, 0.0049]). These findings are useful as a reference for human resource practitioners, managers, and organizations to develop more effective strategies in enhancing employee work engagement through comprehensive organizational support strengthening. The implications of this research demonstrate that the influence of organizational support on work engagement is direct without requiring an increase in insider status feelings first, therefore organizations should prioritize enhancing perceived organizational support directly to improve employee work engagement.